Study Design of the Graft Patency After FFR-Guided Versus Angiography-Guided CABG Trial (GRAFFITI) - Toth, Gabor G; De Bruyne, Bernard; Kala, Petr; Ribichini, Flavio L; Casselman, Filip; Ramos, Ruben; Piroth, Zsolt; Fournier, Stephane; Van Mieghem, Carlos; Penicka, Martin; Mates, Martin; Van Praet, Frank; et al. (Journal of cardiovascular translational research, 2018)
Clinical benefit of invasive functionally guided revascularization has been mostly investigated and proven for percutaneous coronary intervention. It has never been prospectively evaluated whether a systematic fractional flow reserve (FFR) assessment is also beneficial in guiding coronary artery bypass graft surgery (CABG). The objective of the GRAft patency after FFR-guided versus angiography-guIded CABG (GRAFFITI) trial was to compare an FFR-guided revascularization strategy to the traditional angiography-guided revascularization strategy for patients undergoing CABG. Patients were enrolled with significantly diseased left anterior descending or left main stem and at least one major coronary artery with angiographically intermediate stenosis (30-90% diameter stenosis) that was assessed by FFR. Thereafter, while the FFR values were kept concealed, cardiac surgeons decided their intended procedural strategy based on the coronary angiography alone. At this point, patients underwent 1:1 randomization to either an FFR-guided or an angiography-guided CABG strategy. In case the patient was randomized to angiography-guided arm, cardiac surgeons kept their intended procedural strategy, i.e., CABG was guided solely on the basis of the coronary angiography. In case the patient was randomized to the FFR-guided arm, FFR values were disclosed to the surgeons who revised the surgical protocol according to the functional significance of each coronary stenosis. The primary endpoint of the trial was the rate of graft occlusion at 12 months, assessed by coronary computed tomography or coronary angiography. The secondary endpoints were (1) length of postoperative hospital stay; (2) changes in surgical strategy depending upon FFR results (in FFR-guided group only); and (3) rate of major adverse cardiac and cerebrovascular events, i.e., composite of death, myocardial infarction, stroke, and any revascularization during the follow-up period. This study is the first prospective randomized trial investigating potential clinical benefits, associated with FFR-guided surgical revascularization. TRIAL REGISTRATION: NCT01810224.
Keywords: koronární bypass; Treatment Outcome; frakční průtoková rezerva myokardu; jednoduchá slepá metoda; průchodnost cév; Female; Blood Vessel Prosthesis; Follow-Up Studies; Humans; chirurgie s pomocí počítače; následné studie; výsledek terapie; Coronary Angiography; lidé; Coronary Artery Disease; mužské pohlaví; Vascular Patency; Male; ženské pohlaví; nemoci koronárních tepen; Fractional Flow Reserve, Myocardial; prospektivní studie; Coronary Vessels; Prospective Studies; Surgery, Computer-Assisted; koronární angiografie; cévní protézy; Single-Blind Method; koronární cévy; Coronary Artery Bypass